2009
DOI: 10.1186/1471-2407-9-402
|View full text |Cite
|
Sign up to set email alerts
|

Initial activation of EpCAM cleavage viacell-to-cell contact

Abstract: BackgroundEpithelial cell adhesion molecule EpCAM is a transmembrane glycoprotein, which is frequently over-expressed in simple epithelia, progenitors, embryonic and tissue stem cells, carcinoma and cancer-initiating cells. Besides functioning as a homophilic adhesion protein, EpCAM is an oncogenic receptor that requires regulated intramembrane proteolysis for activation of its signal transduction capacity. Upon cleavage, the extracellular domain EpEX is released as a soluble ligand while the intracellular dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 37 publications
1
78
0
Order By: Relevance
“…It has been demonstrated that a proteolytic cleavage of EpCAM by Presenilin 2 releases EpICD, which forms a complex with -catenin and Tcf/Lef leading to an induction of c-Myc and Cyclin A and E expression [371,372].…”
Section: Adherens Complexes In the Context Of -Catenin Signalingmentioning
confidence: 99%
“…It has been demonstrated that a proteolytic cleavage of EpCAM by Presenilin 2 releases EpICD, which forms a complex with -catenin and Tcf/Lef leading to an induction of c-Myc and Cyclin A and E expression [371,372].…”
Section: Adherens Complexes In the Context Of -Catenin Signalingmentioning
confidence: 99%
“…This transcription complex binds the DNA at the lef-1 consensus sites inducing target genes c-myc and cyclin A and E expression [72], and drives cell proliferation. This notion is supported by the EpCAM found in nuclei of colon carcinoma but not of normal tissue [72], and HCT (colon) and MCF-7 (breast) carcinoma cells [65].In addition, analysis for concomitant presence of claudin 7,Co-029,CD44V6 and EpCAM expression in the presence of all four molecules in a complex formation was initially found in colorectal cancer (CRR) and has been shown to facilitate metastasis [108].…”
Section: Epcam Nuclear Signalingmentioning
confidence: 90%
“…EpCAM is a type I transmembrane protein of 314 amino acids (aa)with apparent molecular weight of 40kd [70]. The extracellular domain (EpEX) contain epidermal growth factor-like domain, a thyroglobulin (TY) repeat domain,tansmembrane domain (TM, and a short 26-amino acid intracellular domain (EpICD) (Figure 1) [65,[69][70]. It is encoded by the GA733-2 gene located on the long arm of chromosome 4 [71].…”
Section: Epcam Structurementioning
confidence: 99%
See 2 more Smart Citations